Short Communication: A novel method for parallel measurement of temperature and heat flux with a single layer probe. (April 2022) - Huber, Konstantin; Gackstatter, Felix; Rödiger, Tim
Abstract: In this communication the development and performance of an especially designed parallel impedance evaluation technique for fast heat flux sensors is described. The additional signal depends on the inner resistance of the sensors active layer and is calibrated as temperature measurand. Both parallel measured quantities enable are more precise heat transfer measurement. A response signal of the measurement methodology under a thermal radiative load is provided. Highlights: Combined heat flux and temperature measurement within one sensing element. Parallel high frequency impedance measurement. Impedance-based temperature calibration. Fast heat flux measurement based on the ALTP technique.